Corrosion Behaviors’ Investigation of Carbide Coatings Developed for Sulphuric Acid Recovery Systems - Erhan Özkan (Journal of Advanced Research in Natural and Applied Sciences)
In this study, corrosion resistance of cobalt and nickel, which are known to have high corrosion resistance, reinforced tungsten carbide coatings applied to low carbon stainless steel material surfaces to reduce corrosion-induced losses in sulphuric acid recovery systems were investigated. During the recovery of sulphuric acid, aggressive sulphur systems in the baths cause the metal surface to dissolve and therefore a high amount of material loss occurs. In order to minimize corrosion induced material loss, 316 L stainless steel surfaces were coated with an interlayer of 95% nickel and 5% aluminium alloy, and then tungsten carbide coatings were synthesized on the surfaces of substrate materials reinforced with 13% cobalt and 13% nickel, respectively by thermal spraying method to further reduce the corrosion rate. Characterization of the produced coatings were carried out by X-ray diffraction (XRD), scanning electron microscope (SEM), optical microscope, image analyzer, and surface roughness device. The standard potentiodynamic polarization characteristics of the coatings for 1M H2SO4 solution at room temperature were investigated with a potentiostat/galvanostat device. As the obtained results, nickel reinforced tungsten carbide coatings with nickel aluminium interlayer showed the highest corrosion resistance against sulfuric acid environment with 0,41 mm/year corrosion rate. As a result of the article, the corrosion resistance of 316L stainless steels in sulfuric acid systems was improved by 5.02 and 3.15 times, respectively.